Effects of Different Coating Agents on the Storage Quality of Fresh-cut Celery - Xinhui SUN; Junpeng LI; Qing HU; Xiaofeng CHEN (Guangdong nongye kexue, 2025)
【Objective】By studying the changes of different coating agents on the quality of fresh-cut celery during storage, this study investigated the effect of a novel plant immune initiating protein, Heminsu (HMS), on its storage quality, and provided a theoretical basis for the practical application of HMS.【Method】Fresh-cut celery was respectively treated with chitosan (CTS), salicylic acid (SA) and HMS coating and stored at 15℃ for 5 days. The changes in weight loss rate, browning index, chlorophyll content, soluble solid content, soluble protein content, catalase (CAT) activity, NAD-malate enzyme (NAD-ME) activity, NAD-malate dehydrogenase (NAD-MDH) activity and shelf-life were investigated.【Result】After 5 days of storage, the weight loss rates of fresh-cut celery in CTS, SA and HMS groups were 0.60%, 0.63% and 0.76%, respectively, which were lower than that of the CK group (0.80%), but the difference between the CK group and the HMS group was not significant (P > 0.05). The browning index of the HMS group was significantly lower than that of the CK group, which was 90.22% of that of CK group, and that of CTS group was significantly higher than CK group (P < 0.05). The HMS coating treatment significantly inhibited the decrease of chlorophyll content, and the chlorophyll content of the HMS group was 1.41, 1.85 and 1.42 times higher than that of the control group on 1 day, 3 days, 5 days, respectively. On day 1 of storage, the soluble solids content of the SA and HMS groups was 4.13% and 4.10%, respectively, which were significantly different from that of the CK group. During the storage period, the soluble protein content of all groups exhibited an initial increase followed by a decrease. On day 3 and day 5 of storage, the soluble protein content of the HMS group was significantly higher (P < 0.05) than that of the CK group, with an increase of 10% and 30%, respectively. After 5 days of storage, the CAT activities of CTS, SA and HMS groups were significantly higher than those of the CK group, which increased by 84%, 100% and 76%, respectively, with better antioxidant capacity. HMS coating treatment could reduced NAD-ME activity to 76.19%, 62.50% and 93.33% of that of the CK group on day 1, day 3 and day 5 of storage, respectively; NAD-MDH activity of the HMS group was 65.08% and 67.54% of that of the CK group on day 1 and day 5 of storage, respectively. When weight loss, browning index, and chlorophyll content were used as evaluation criteria, the HMS coating treatment extended the shelf life of fresh-cut celery by 0.1 days, 4.6 days, and 3.1 days, respectively.【Conclusion】HMS coating treatment can prolong the shelf-life of fresh-cut celery, maintain the nutritional value and flavor of fresh-cut celery to a certain extent, improve the antioxidant capacity, regulate the activity of energy metabolism-related enzymes, and help to improve the storage and preservation effect of fresh-cut celery.